2011
DOI: 10.2139/ssrn.1808845
|View full text |Cite
|
Sign up to set email alerts
|

Individual Expectations, Limited Rationality and Aggregate Outcomes

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 32 publications
4
52
0
Order By: Relevance
“…The fundamental trader thus acts as a "far from equilibrium" stabilizing force in the market, mimicking the feature that more traders in the market expect the price to return in the direction of the fundamental when the deviations becomes large 8 . Subjects' earnings depend on forecasting performance and are given by a quadratic scoring rule…”
Section: Experimental Designmentioning
confidence: 99%
“…The fundamental trader thus acts as a "far from equilibrium" stabilizing force in the market, mimicking the feature that more traders in the market expect the price to return in the direction of the fundamental when the deviations becomes large 8 . Subjects' earnings depend on forecasting performance and are given by a quadratic scoring rule…”
Section: Experimental Designmentioning
confidence: 99%
“…Bostian and Holt, 2009). Heemeijer et al (2009) and Bao et al (2012) investigate whether the non-convergence result is driven by the positive expectation feedback nature of the experimental market. Positive/negative expectation feedback means that the realised market price increases/decreases when the average price expectation increases/decreases.…”
mentioning
confidence: 99%
“…The experiments in Hommes, Sonnemans, Tuinstra, and van de Velden (2005), henceforth HSTV05, showed that the subjects can coordinate on oscillating and serially correlated time series, and that convergence to the fundamental equilibrium happens only under severe restrictions on the underlying law of motion. Further experiments in Heemeijer, Hommes, Sonnemans, andTuinstra (2009), henceforth HHST09, andBao, Hommes, Sonnemans, andTuinstra (2012), henceforth BHST12, demonstrated that the expectations feedback structure plays crucial role. Negative feedback systems (i.e., where more optimistic forecasts lead to lower market prices, as in supply driven commodity markets) tend to generate convergence to the fundamental equilibrium rather easily, while positive feedback systems (i.e., where more optimistic forecasts lead to higher market prices, as in speculative asset markets) typically generate behavior with the price oscillating around the fundamental equilibrium dynamics.…”
mentioning
confidence: 99%